Restauração ecológica por semeadura direta: trajetória e análise multicriterial - Costa, Glória Fabiani Leão da (Universidade Federal de São Carlos, 2024)
Direct seeding is a promising and constantly evolving forest restoration technique. Monitoring your trajectory is essential to identify gaps and improvements. This work was divided into two stages, where, in Chapter 1, we sought to analyze the trajectory of a direct seeding area over 60 months; and in Chapter 2, evaluate whether direct seeding was efficient in restoring ecological processes essential for its stability, resilience and reliability. For the trajectory, monitoring was carried out at 30 days, 24 and 60 months in permanent plots, the composition, diversity, phytosociology and dynamics were evaluated. To evaluate ecological functions, a protocol based on the MESMIS method was used, obtaining the Ecological Functionality Consolidation Index (EFCI), with 25 indicators, defined by descriptors and reference scenarios. Sowing (SD) was compared with areas of forest remnants (AR) and restoration area by planting seedlings (RAD). At 60 months, the area had a density of 14,031 plants.ha-1. The plant assemblage was able to maintain the composition of established species, with an increase in richness (S=36), without the exclusion of any. SD presented higher values in the descriptors of soil fertility (0.07 SD; 0.06 RAD; 0.08 AR) and functional diversity (0.08; 0.06; 0.15) compared to RAD, but demonstrated the lowest value for community diversity (0.06; 0.07; 0.10), control and management (0.06; 0.08; 0.37) and soil and litter protection (0.15; 0. 17; 0.23). Over 60 months, the trajectory of the plant assemblage demonstrated stability in its composition, enabled the entry of new species, and presented a structure similar to natural forests in the initial stage of succession. SD demonstrated potential for the return of ecological functions, requiring the inclusion of adaptive management and continuous monitoring in the coming months.
Ecological restoration by direct seeding: trajectory and multicriteria analysis
Keywords: Dinâmica; Indicadores ambientais; Monitoramento; Processos ecológicos; Dynamics; Ecological processes; Environmental indicators; Monitoring; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA